Identification of Breeding Colonies of Lesser Adjutant Stork (Leptoptilos javanicus) Horsfield, 1821 in Jharkhand, India - Xaxa, Sanjay; Sharma, Chandra; Kumar, Rajnish; Agarwal, Prawesh; Kumar, Arvind; Bilal, Ahmad; Kumar, Avinash; Thakur, Dashrath (Indian Forester, 2024)
A study was undertaken to investigate the occurrence of Lesser Adjutant Stork (Leptoptilos javanicus) (LAS) in different districts of Jharkhand during December 2022 to February 2023. The survey provided positive results with a record of four breeding colonies from the study. The first breeding colony was observed at Jamtara village in Giridih district with 6 nests, second breeding colony was observed at Thana Ckowkin Giridih district with 2 nests, the third and fourth breeding colonies were observed at Jarangdih village and Kodwadih village in Bokaro district with 5 and 2 nests respectively. The area is suitable for the species in terms of habitat, however anthropogenic threats still exist and require conservation interventions. Atotal number of 52 individuals and 15 nests of LAS were observed. Among 52 individuals 26 were fledglings/juveniles and 26 were adult individuals. Amongst the 15 breeding nests,9 were found on 5 different tall Bombax ceiba (Semal) trees and 6 on a single Ficus bengalensis (Bargad) tree. All the nests were occupied with fledglings ranging from one to two fledglings per nest. The largest breeding colony was observed on a single Ficus bengalensis (Bargad) tree at Jamtara village in Dumri block of Giridih district and the smallest breeding colony was observed on Bombax ceiba (Sembal) trees at Kodwadih village in Nawadih block of Bokaro district, that needs to be protected.